The Status of Translators and Interpreters in Korea - Choi, Jungwha; Lim, Hyang-Ok (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThe status of interpreters and translators depends on the society in which they belong. Such factors as whether the society is multilingual, monolingual as well as its international standing all impact their status and consequently financial compensation. A brief overview of the history of the status of Korean interpreters reveals that, in the past, they enjoyed middle class status and, at times, even great wealth. The social importance of translators, on the other hand, was negligible—a situation which was aggravated by the fact that readers were not very demanding. During the modern era, and especially with increased foreign trade in the 1980’s, however, such tolerance was no longer the norm. There is still great interest among the general public in interpretation, especially since speaking English fluently is considered an asset in any profession in Korea. Conference interpreters, as such, are considered to be “master” English speakers. While they are envied their fluent mastery of foreign languages, interpretation, as such, is not considered a profession in which one should devote one’s life. In the case of translation, though there are many translators, they are held in even lower esteem than interpreters because of the relatively low pay.